Textiles in sport - Shishoo, Roshan (Woodhead Pub. in association with the Textile Institute ; CRC, 2005)
The technical developments in the sports clothing industry has resulted in the use of functional textiles for highly-specialised performances in different sports. Developments include thermal and functional properties and coated and laminated clothes. With bio- and smart materials providing such a strong focus in the textile industry generally, companies are going for 'value-added' textiles, such as in-built sensors which monitor performance. In-built wear comfort is a growing market trend and includes clothing which improves the skin's performance. Written by a distinguished editor and a team of authors from the cutting edge of textile research, Textiles in sport discusses high-performance, high-function and intelligent textiles for sportswear. Invaluable for a broad range of readersDiscusses high-performance, high-function and intelligent textiles for sportswear.
Keywords: Sport clothes.; Sporting goods -- Materials -- Research.; Textile fabrics -- Technological innovations.; elektronické knihy; electronic books